Concentración de clorofila a en colonias de Pocillopora verrucosa (Sderactina) durante un blanqueamiento coralino en el Golfo de California, México (1997) - Munguía-Vega, Adrián (Universidad de Costa Rica, 1999)
El Niño-Southern Oscillation 1997-98 significantly elevated sea temperatures in the Gulf of California and caused widespread coral bleaching starting in july 1997. Changes in chlorphyll a concentration by unit of area (cm2) among normal, discolored and totally bleached colonies of the coral Pocillopora verrucosa (=P. elegans) were determined in 27 colonies collected in october, 1997 al Ensenada de Muertos. Baja California peninsula, México (240 03' N), by spectrophotometric determinations. Mean pigment values varied from 2.06 ¡..tg/cm2 to 1.12 ¡..tg/cm2 and 0.09 Ilg/cm2 among normal, decolorated and totally bleached colonies, respectively, although statistically significant differences only appeared between completely bleached and normal corals. The low chlorophyll concentration of the healthy-Iooking ("normal") corals and the lack of differences in pigment concentrations between these and partially bleached corals, indicated that the former had actually suffered a previous loss of pigmentation and may have been recovering when sampled.